Hubungan Tingkat Pengetahuan Kader Posyandu Dengan Keaktifan Kader Dalam Kegiatan Posyandu Bayi Balita Di Desa Kebarongan Kecamatan Kemranjen - Ngafiatu Rahayuningsih; Wulan Margiana (2023)
In order to minimize the number of infant and toddler deaths is by implementing integrated service posts (Posyandu). The active role of cadres determines the success rate of posyandu, so that the factors that cause cadre inactivity need to be addressed. This research is to understand the relationship between the level of posyandu cadres and the activity of cadres in the activities of posyandu for toddlers in Kebarongan Village, Kemranjen District. This study used a comparative unpaired categorical research design with a cross-sectional approach. The population of all cadres in Kebarongan Village, Kemranjen District in July. The data source used is primary data which is taken using a questionnaire about the level of knowledge of cadres with a sample of 47 posyandu cadres for infants under five taken by purposive sampling. The analysis technique with the chi square test is the relationship between the level of knowledge and the activity of cadres in Posyandu activities for babies under five in Kebarongan, Kemranjen sub-district. The results of the study showed a p-value of 0.004 <0.05, which means that there is a significant relationship between the knowledge level of cadres and their activeness in posyandu activities.